Endometrial Stem/Progenitor Cell Markers in Polycystic Ovary Syndrome (PCOS) versus Non-PCOS Infertile Women: A Systematic Review of Molecular and Cellular Signatures - Dr Amit Patil; Dr Hemant Deshpande (The Bioscan, 2026)
The human endometrium is a highly regenerative tissue whose cyclical renewal is driven by endometrial stem/progenitor cells, critical for successful implantation and fertility. Polycystic Ovary Syndrome (PCOS), a prevalent endocrine disorder, disrupts endometrial structure and function, potentially through altered stem/progenitor cell activity. This systematic review aimed to compare the expression of key endometrial stem/progenitor markers—CD146, SUSD2, Lgr5, SSEA-1, and N-cadherin—between infertile women with and without PCOS. A comprehensive search of PubMed, Cochrane, and ScienceDirect from 2015 to 2025 identified 20 eligible studies meeting strict inclusion criteria. Findings consistently revealed dysregulation of stromal and epithelial progenitor markers in PCOS, including reduced CD146/SUSD2 and altered Lgr5, SSEA-1, and N-cadherin expression, associated with impaired stromal remodeling, epithelial renewal, and implantation potential. These molecular alterations likely contribute to infertility and endometrial dysfunction in PCOS. Future research should integrate functional assays and longitudinal studies to clarify causal mechanisms and therapeutic targets